ADCP data from lander deployment DOS1 during SONNE cruise SO242/1 in the DISCOL area - Jens Greinert (PANGAEA, 2018)
Deep-Sea Observation System (DOS) lander from GEOMAR was deployed in the DISCOL Experimental Area (DEA) for a short duration of 4 days (2015-07-30 to 2015-08-03). This dataset contains raw and processed data from 300kHz upward looking ADCP.